Strategi dan Distribusi Harga Produk Pegadaian Syariah dalam Meningkatkan Ekonomi Umat - Muhammad Yudha Ardiansyah; Muhamad Zen; Fatmawati Fatmawati (Moneter : Jurnal Ekonomi dan Keuangan, 2025)
Pegadaian Syariah plays an important role in strengthening the people's economy through the provision of financial services in accordance with Sharia principles. This study aims to analyze the pricing and distribution strategies of Pegadaian Syariah products and their impact on the economic growth of the community. The research method uses a qualitative approach based on literature studies and secondary data analysis. The results of the study show that Pegadaian's Sharia pricing strategy pays attention to the principles of justice and affordability, while product distribution is carried out through service digitalization, expansion of branch office networks, and strategic partnerships. The use of these two strategies has proven effective in increasing the accessibility of Pegadaian Syariah services, accelerating financial inclusion, and encouraging the growth and empowerment of micro, small, and medium economies based on Sharia.